Production Methods and Internships in Vocational Education - J. P., Turdiyev (European Journal of Life Safety and Stability (2660-9630), 2021)
In this article, the content of industrial and educational practice in vocational education is described as an integral process and result, expressed in the aggregate of its basic terms and concepts. Industrial and pedagogical practice in vocational education, the main goal and function of education is to form the foundations of professional skills in the chosen profession (specialty) among students, and the future in their profession is an expression of the transition from practical training to professional labor activity. It is also emphasized that knowledge by profession (specialty) will be provided for the formation of the relevant necessary skills in the process of training in production and teaching practice.